Thermodynamic properties of iron, aluminum, boron and phosphorus in dilute silicon solutions by molecular interaction volume model (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
The thermodynamic properties of impurity components in silicon solution play an important role in chemical removal process to the metallurgical route. In this paper, the component activity coefficients and interaction parameters of dilute silicon solutions were estimated by the molecular interaction volume model (MIVM). The activity coefficients ( ) of component i in dilute binary Si-i and ternary Si-i-j solutions at 1687-1873 K were firstly calculated. The concentration dependences of interaction parameter and activity coefficient were also obtained. The self-interaction parameters ( ) for Si-i system were obtained as , , and . At the same time, the interaction parameters among components B, Al and Fe in dilute ternary Si-i-j solutions were also derived as , and . Most important of all, the temperature dependences of interaction parameters and activity coefficients in dilute Si-i and Si-i-j solutions with a certain i or j concentration were deduced. The results show that the predicted self-interaction parameters of B, Al, Fe and P in binary silicon solutions are in reasonably agreement with experimental data. This further shows that MIVM is of reliability and can be expanded to a multi-component dilute silicon solution.